First report of the spider genus Desis (Araneae, Desidae) from China, with description of a new species - Lin, Yejie; Li, Shuqiang; Chen, Haifeng (Zootaxa, 2020)
The spider genus Desis Walckenaer, 1837 is the type genus of the spider family Desidae Pocock, 1895. Desis spiders hide in silk sacs between rocks or shells during high tide and forage during low tide (Baehr et al. 2017). Four Desis species have been recorded from Asia: Desis gardineri Pocock, 1904 (India), Desis inermis Gravely, 1927 (India), Desis japonica Yaginuma, 1956 (Japan) and Desis martensi L. Koch, 1872 (Malaysia) (World Spider Catalog 2020). Until now, only one species of the family Desidae, Badumna tangae Zhu, Zhang & Yang, 2006, has been reported from China (Zhu et al. 2006). Here, we describe a new species of Desis and report the genus from China for the first time.